2018
DOI: 10.26434/chemrxiv.7294388.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De Novo Generation of Hit-like Molecules from Gene Expression Signatures Using Artificial Intelligence

Abstract: Finding new molecules with a desired biological activity is an extremely difficult task. In this context, artificial intelligence and generative models have been used for molecular <i>de novo</i> design and compound optimization. Herein, we report the first generative model that bridges systems biology and molecular design conditioning a generative adversarial network with transcriptomic data. By doing this we could generate molecules that have high probability to produce a desired biological effec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Molecular Embedding: Recent studies have shown that is possible to encode molecules (as SMILES 34,44,45 , graphs or SELFIES 36 ) into a continuous representations. As before 34,45,46 , we used a molecular autoencoder but in this case it learns to encode SELFIES of a molecule (as one-hot encoding) into a continuous latent vector, which then can be decoded back into SELFIES. The architecture of this model is based on the previous work of Winter et al 34,45 ,…”
Section: Methodsmentioning
confidence: 99%
“…Molecular Embedding: Recent studies have shown that is possible to encode molecules (as SMILES 34,44,45 , graphs or SELFIES 36 ) into a continuous representations. As before 34,45,46 , we used a molecular autoencoder but in this case it learns to encode SELFIES of a molecule (as one-hot encoding) into a continuous latent vector, which then can be decoded back into SELFIES. The architecture of this model is based on the previous work of Winter et al 34,45 ,…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the DINGOS algorithm combines a rule‐based approach with an ML model trained on known successful synthetic routes, while the former ensures the synthesizability and the later provides a directed approach to limiting the output molecules to compounds with desirable similarity to the template. Another remarkable ML‐based generative approach is proposed by Méndez‐Lucio et al, 261 which bridges systems biology and molecular design. To our knowledge, it is the first AI/ML‐based drug design tool that combines transcriptomic and structural data.…”
Section: Ai/ml Applications In Drug Discoverymentioning
confidence: 99%
“…Mendez-Lucio et al of Bayer combined GAN with transcriptomic data and demonstrated its capabilities in proposing hit molecules based on a gene expression signature of the target knockout. 56 This approach was based on the concept that a knocked-out protein would generate a gene expression signature that is analogous to the pharmacological inhibition of the same target. This platform could be applied to any target, as no prior background information on it or its active molecules are required.…”
Section: Application Of Ai In Drug Discoverymentioning
confidence: 99%